Compact city and sustainable high-density living - Bay, Joo (Eathscan From Routledge, 2017)
The fear of density is real, and so is the perpetual infatuation for sprawl. What do people really want? Do they simultaneously desire privacy, security and a sense of belonging to a community? Do they want the convenience of the city, and ye the personal open space for recreation? If personal open space is what people want, could a focus on creating ‘garden land’ for such spaces in the sky be more accurate in meeting needs besides creating apartment units in the sky? This chapter begins with the concept of the ‘Third Ecology’ in the Shape of Community, where the ultimate resilient ecology is one where the human potential, nature and technological environments are balance and optimised. The chapter then discusses the dichotomy in practice between the efforts to promote environmental sustainability and social sustainabil-ity, and describes a certain socio-environmental correlation found in residential cases in both Singapore and Perth. The chapter then compares what people really want in Perth to what the market tends to provide. It is suspected that the existing real-estate valuation system does not represent the true housing desires of the Perth population. Consequently, as long as the city does not understand and provide for what people really want, it will be difficult to attract people who have little choice but continue with sprawl – the principles of a higher-density compact city cannot be realized effectively. In conclusion, the chapter suggests a more holistic methodology to study real wants that inform a more inclusive and accurate valuation system, allowing city councils, developers, financier, sellers and buyers to make more informed and sustainable decisions for the future.